Simply Bells and Whistles?: Cognitive Effects of Visual Aesthetics in Digital Longforms. Issue 2 (7th February 2019) - Greussing, Esther; Boomgaarden, Hajo G.
Abstract : The success of digital longforms in terms of readership and viral spread promotes an optimistic perspective on innovative web journalism with regard to the attention, engagement, and subsequent knowledge acquisition of citizens when consuming news. Since empirical evidence for such effects is scant, this experimental study focuses on visual aesthetics as a signature element of novel news formats that are designed to attract attention in a highly competitive media landscape. Specifically, it draws on the theoretical framework of user engagement and shows that the presence of visual aesthetics contributes to meaningful learning from the news by initiating positive attitudes towards the interface, which in turn leads to deeper involvement with the content. However, when the presence of visual aesthetics fails to affect interface evaluation, the opposite effect occurs. Surprisingly, these effects are not found to be contingent upon individual differences such as issue involvement or issue-specific prior knowledge. Overall, our results suggest that for news organizations, it is worth investing financial and personal resources in innovative news formats in order to support knowledge gain, although they need to be carefully designed as the first encounter with the interface decides about the subsequent engagement with and processing of the news.